Dynamics of the Philippine market sectors a DDC analysis - Gordo, Gilbert M.
Aims to describe market sector volatility behavior in the Philippines. Examines the behavior market sector indices (financials, industrial, holding firms, property, services and mining &oil) using dynamic conditional correlation (DCC) analysis, a multivariate GARCGH model. Also shows how the DCC is used for firm level data.